Cost-effectiveness of transcatheter aortic valve replacement in patients ineligible for conventional aortic valve replacement. Issue 5 (10th November 2011) - Watt, Maureen; Mealing, Stuart; Eaton, James; Piazza, Nicolo; Moat, Neil; Brasseur, Pascale; Palmer, Stephen; Busca, Rachele; Sculpher, Mark
Abstract : Objective: To assess the cost-effectiveness of transcatheter aortic valve implantation (TAVI) compared with medical management in patients with severe aortic stenosis who are ineligible for conventional aortic valve replacement (SAVR) from the perspective of the UK National Health Service. Design: Probabilistic decision analytical model. Methods: A decision analytical model was developed to assess the costs and benefits associated with both interventions over a 10-year time horizon. A literature review was performed to identify relevant clinical evidence. Health-related quality of life and mortality were included using data from the PARTNER clinical trial (cohort B). Unit costs were taken from national databases. Costs and benefits were discounted at 3.5% per year, and extensive sensitivity analyses (probabilistic and deterministic) were performed to explore the impact of uncertainty on the cost-effectiveness estimates. Main outcome measure: Incremental cost-effectiveness ratio (ICER) with benefits expressed as quality-adjusted life years (QALYs). Results: The base case ICER was approximately £16 100 per QALY gained. At a cost-effectiveness threshold of £20 000 per QALY gained, the probability that TAVI was cost-effective compared with medical management was 1.00. The results were robust to changes in key clinical parameters as well as choice of baseline survival data. The observed PARTNER survival data only have to be extrapolated for 2 years to generate an ICER below £30 000 per QALY gained, which is the upper value of the threshold range used by the National Institute for Health and Clinical Excellence in the UK. Conclusions: TAVI is highly likely to be a cost-effective treatment for patients with severe aortic stenosis who are currently ineligible for SAVR.